Effect of Drying Method and Temperature on the Quality of Cascara Tea - Tampubolon, Sanggam Dera Rosa; Seleleubajak, Monica Brunelly; Nurhayati, Nurhayati (Agro Bali : Agricultural Journal, 2024)
This study aims to determine the effect of the drying method and optimum temperature on the quality of coffee skin tea (cascara). This research was conducted at the Laboratory of Food Processing Technology and Agricultural Products, Department of Agricultural Products Technology, Faculty of Agriculture, Santo Thomas Catholic University, Medan. This research was conducted in March 2023 until completion. This research was conducted using a completely randomized design (CRD), which consisted of 2 factors. The first factor is the drying method (P), namely L : P1 = 4 hours, P2 = 6 hours, P3 = 8 hours and P4 = 10 hours. The second factor is the effect of drying temperature on the quality of tea from coffee skin (T), namely: T1 = 40°C, T2 = 50°C, T3 = 60°C and T4 = 70°C. The results showed that the drying method had a very significant effect (p<0.01) on the yield, water content, polyphenol content, organoleptic value of taste, organoleptic value of aroma and color organoleptic value of cascara tea produced. The longer drying time, the yield and organoleptic value of flavor increase, while the water content, polyphenol content, organoleptic value of aroma and organoleptic value of cascara tea produced decreases. The drying temperature has a very significant effect (p<0.01) on yield, moisture content, polyphenol content, the organoleptic value of taste, the organoleptic value of aroma, and organoleptic value of color. The higher the drying temperature, the higher the yield and taste organoleptic value, while the water content, polyphenol content, aroma organoleptic value and color organoleptic value decreased. The interaction of the drying method and temperature treatment had a significant effect (p<0.015) on the moisture content, polyphenol content, and aroma organoleptic value of cascara tea but had no significant effect (p>0.05) on yield, taste organoleptic value, and color organoleptic value of coffee skin tea (cascara). The best quality of cascara tea was obtained in the treatment combination P1T4.